2008
DOI: 10.1186/1471-2164-9-217
|View full text |Cite
|
Sign up to set email alerts
|

Biocomputational prediction of small non-coding RNAs in Streptomyces

Abstract: Background: The first systematic study of small non-coding RNAs (sRNA, ncRNA) in Streptomyces is presented. Except for a few exceptions, the Streptomyces sRNAs, as well as the sRNAs in other genera of the Actinomyces group, have remained unstudied. This study was based on sequence conservation in intergenic regions of Streptomyces, localization of transcription termination factors, and genomic arrangement of genes flanking the predicted sRNAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
62
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 38 publications
3
62
0
Order By: Relevance
“…As mentioned in the introduction, two studies of sRNAs in S. coelicolor A3(2) were reported during our study of sRNA in S. griseus (23,27). Panek et al (23) validated the expression of 20 sRNAs by RT-PCR and DNA microarray analyses.…”
Section: Vol 191 2009mentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned in the introduction, two studies of sRNAs in S. coelicolor A3(2) were reported during our study of sRNA in S. griseus (23,27). Panek et al (23) validated the expression of 20 sRNAs by RT-PCR and DNA microarray analyses.…”
Section: Vol 191 2009mentioning
confidence: 99%
“…The complete genome sequences of several species of Actinobacteria, including two Streptomyces species, S. coelicolor A3(2) (3) and Streptomyces avermitilis (11), facilitated bioinformatics prediction of candidate regions for sRNAs in Streptomyces. Recently, two studies (23,27) reported the identification of sRNAs in S. coelicolor A3(2). Panek et al (23) predicted 32 potential sRNAs, and the expression of 20 of them was detected by reverse transcription (RT)-PCR and DNA microarray analyses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Combinations of bioinformatic predictions and experimental approaches have facilitated the identification of many sRNAs in S. coelicolor and other species (52,(269)(270)(271), and what little is known about their functions points to a boost in the perceived importance of sRNA-mediated regulation of antibiotic production in the near future. Thus, the overexpression of scr5239, an sRNA recently identified in S. coelicolor, decreased ACT production, whereas depletion of scr5239 increased production (272), and overexpression of cnc2198.1as significantly decreased RED production (273).…”
Section: Srnasmentioning
confidence: 99%
“…RNAz classifies multiple sequence alignments into ncRNA/non-ncRNA based on the detection of significant conserved secondary structure and base pair (bp) covariation. It has been applied to several organism families, including bacteria, where it led to experimental confirmation of novel ncRNAs (del Val et al 2007;Panek et al 2008;Sonnleitner et al 2008). We compared NAPP clustering and RNAz in their abilities to distinguish true ncRNAs from other conserved elements.…”
Section: Performance Of Napp As An Ncrna Classifiermentioning
confidence: 99%